Diagnóstico ambiental da bacia hidrográfica do córrego do Bugre em Alumínio - SP - Tersariol, Pedro Paulo dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The human growth that has occurred after the Industrial Revolution and the postwar period has been drastically pressing natural resources. Alumínio - SP, the major urban area of this municipality is condensed in the sub-basin of the Bugre stream, rather compromising the quality of its waters, especially in the urban area. In this sense, the environmental assessment is key to monitoring and understanding of the status and quality of exploited natural resources and aid decision making. This work conducted over a seasonal year, the diagnosis of water quality in three Bugre Stream points via parameters contemplated in IVA (the Water Quality Index for the Aquatic Life Protection and Water Communities) and IQA (Index Quality of the Waters) CETESB. The first point is located at the source (the area with native vegetation) the second and third are situated in urban area. Parameter data were statistically analyzed according to the Principal Component Analysis (PCA). According to the evaluations of points were notable variations in water quality between the three points analyzed, which occurred due to their geographical locations as well as the influence of seasonality in the concentration of pollutants. The second and third point showed very high levels of various contaminants, highlighting the phosphorus and total nitrogen, surfactants, fecal coliforms and chlorophyll-a as well as certain types of metals such as copper and lead. The ACP indicated that the IET (Trophic State Index) was related mainly with phosphorus, IQA (Water Quality Index) with the OD and IPMCA (Minimum Variable Index for the Protection of Aquatic Life) with the presence of surfactants. The results highlight the need for recovery of their physicochemical and microbiological characteristics in urban area. Solutions such as sewage treatment are essential for this recovery. Environmental planning (supported by environmental zoning) within the decision-making by the government ...

O crescimento humano que vem ocorrendo após a Revolução Industrial e ao período do pós-guerra vem pressionando drasticamente os recursos naturais. Em Alumínio - SP, a grande concentração urbana deste município está adensada na sub-bacia do córrego do Bugre, comprometendo bastante a qualidade de suas águas, principalmente em perímetro urbano. Neste sentido, o diagnóstico ambiental é fundamental para o acompanhamento e compreensão do estado e da qualidade dos recursos naturais explorados e no auxílio da tomada de decisões. Este trabalho realizou, ao longo de um ano sazonal, o diagnóstico da qualidade da água em três pontos do córrego do Bugre através de parâmetros contemplados no IVA (Índice de Qualidade das Águas para Proteção da Vida Aquática e das Comunidades Aquáticas) e IQA (Índice de Qualidade as Águas) da CETESB. O primeiro ponto localiza-se na nascente (área com vegetação nativa) o segundo e terceiro estão situados em perímetro urbano. Os dados dos parâmetros foram analisados estatisticamente de acordo com a Análise dos Componentes Principais (ACP). Segundo as avaliações dos pontos, foram notáveis as variações da qualidade da água entre os três pontos analisados, as quais ocorreram devido as suas diferentes posições geográficas e também a influência da sazonalidade na concentração das substâncias poluentes. O segundo e terceiro ponto apresentaram níveis muito elevados de vários contaminantes, destacando-se o fósforo e nitrogênio totais, surfactantes, coliformes fecais e clorofila-a, além de alguns tipos de metais, como o cobre e chumbo. A ACP indicou que o IET (Índice de Estado Trófico) se relacionou principalmente com o fósforo, o IQA (Índice de Qualidade da Água) com o OD e IPMCA (Índice de Variáveis Mínimas para a Proteção da Vida Aquática) com a presença de surfactantes. Os resultados evidenciam a necessidade de recuperação de suas características físico ...
Keywords: Bacias hidrograficas; Água - Qualidade; Alumínio (SP)